2010
DOI: 10.1016/j.yjmcc.2010.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological remodeling in heart failure

Abstract: Heart failure affects nearly 6 million Americans, with a half-million new cases emerging each year. Whereas up to 50% of heart failure patients die of arrhythmia, the diverse mechanisms underlying heart failure-associated arrhythmia are poorly understood. As a consequence, effectiveness of antiarrhythmic pharmacotherapy remains elusive. Here, we review recent advances in our understanding of heart failure-associated molecular events impacting the electrical function of the myocardium. We approach this from an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 254 publications
(249 reference statements)
2
101
0
Order By: Relevance
“…It has been shown that heart failure originates at the cellular scale [28,29,30]. Alterations in ionic currents and calcium handling lead to a prolonged action potential, a lower …”
Section: Heart Failurementioning
confidence: 99%
“…It has been shown that heart failure originates at the cellular scale [28,29,30]. Alterations in ionic currents and calcium handling lead to a prolonged action potential, a lower …”
Section: Heart Failurementioning
confidence: 99%
“…Because transmural gradients of repolarization are major factors influencing vulnerability to cardiac arrhythmias, 84,119,120 proper establishment and maintenance of electric gradients within the ventricular wall are clearly of great interest and importance. In particular, enhanced dispersion of repolarization is associated with several forms of lifethreatening reentrant and torsade-related ventricular arrhythmias, as occur in long-QT, short-QT, and Brugada syndromes, as well as catecholaminergic polymorphic ventricular tachycardia.…”
Section: Relationship Of Irx Genes To Cardiovascular Diseasementioning
confidence: 99%
“…84 In addition, heart disease is accompanied by electric remodeling, which is usually characterized by elevated heterogeneity of repolarization and increased susceptibility to arrhythmia. 120 Interestingly, reduced transmural repolarization gradients can also occur in some heart failure patients, 121 which may explain the increased susceptibility of Irx5 KO mice to arrhythmias, although these mice also show reduced refractoriness, 16 a condition strongly linked to arrhythmia vulnerability. 122 Thus, it is conceivable that changes in expression or mutations of IRX5 may be linked to cardiac arrhythmia in human.…”
Section: Relationship Of Irx Genes To Cardiovascular Diseasementioning
confidence: 99%
“…The mechanical and electrical activation of the heart is in part dependent on the spatial distribution of GJs (22). Changes in GJ patterning and expression level can result in the development of arrhythmias in numerous cardiovascular diseases (23)(24)(25). The alteration in the expression level and spatial distribution of Cx43 in the hypertrophic myocardium suggests that this protein is influenced by ventricular remodeling (18).…”
Section: A B C D Ementioning
confidence: 99%